Risk factors for transplant renal artery stenosis after live donor transplantation. Issue 3 (22nd October 2018) - Nicholson, M. L.; Yong, C.; Trotter, P. B.; Grant, L.; Hosgood, S. A.
Abstract : Background: Renal transplant surgeons are making increasing use of live donor kidneys with multiple renal arteries. This study aimed to identify independent risk factors for the development of transplant renal artery stenosis (TRAS) in the modern era of complex arterial reconstruction for multiple vessels. Methods: Multivariable logistic regression analysis with a stepwise variable deletion model was used to identify risk factors for the development of TRAS in a consecutive series of live donor kidney transplants. Results: Of 506 kidney transplants, 19 (3·8 per cent) had evidence of significant TRAS on CT angiography. Functional TRAS, defined by improvement in BP control or renal function after correction of a stenosis by angioplasty, occurred in 13 of 506 patients (2·6 per cent). Independent risk factors for TRAS were: use of an explanted internal iliac artery graft from the recipient (odds ratio (OR) 4·95; P = 0·020) and total ischaemia time (OR 1·82; P = 0·010). TRAS was associated with a lower 5‐year allograft survival rate (79 versus 88·7 per cent; P = 0·020) but only one graft loss was attributed directly to TRAS. The 5‐year allograft survival rate after internal iliac artery grafting was 86 per cent. Conclusion: Although use of an internal iliac artery graft is an independent risk factor for TRAS after live donor kidney transplantation, this technique is still a useful option for complex arterial reconstruction. Abstract : Rare, but predictable